Penerapan Sistem Informasi Akuntansi Berbasis Komputer Dalam Pengambilan Keputusan Guna Meningkatkan Efektifitas Pendapatan Pada Lembaga Penyiaran Publik Radio Republik Indonesia (Lpp Rri) Stasiun Sumenep - Alwiyah Alwiyah; Achmad Baihaki (AKRUAL: JURNAL AKUNTANSI, 2012)
AbstractThe Target of this research is to know the application of computerized accounting information system for decision-making and to improve the effectiveness of Lembaga Penyiaran Publik Radio Republik Indonesia (LPP RRI) Stasiun Sumenep. By using the computer application system will be carried out in several stages of decision-making, the stages are: recognize and define the problem, identify any alternative as a viable solution, identify the costs and benefits associated with each alternative is feasible, calculate total relevant costs and benefits of each alternative, assessing the qualitative factors, establishing an alternative that offers the greatest benefit. After an analysis of the effectiveness of revenue in the period 2008 and 2009 by using the profit centre method, we conclude that using a computerized system on LPP RRI Stasiun Sumenep calculation of the effectiveness of income more effectively in 2009 than in 2008, which at the time was still using manual systems. It also results in an increase in revenue in 2009 amounted to 2.57%, thus the application of the system of computer-based application that provides a very good impact on revenue in the LPP RRI Stasiun Sumenep.